PELAKSANAAN HAK POLITIK PEMILIH DISABILITAS DALAM PEMILU SERENTAK TAHUN 2019 DI KABUPATEN TANAH DATAR MENURUT UNDANG-UNDANG DISABILITAS DAN FIQH SIYASAH DUSTURIYAH - Marlindawati Marlindawati; Ulya Atsani (Institut Agama Islam Negeri Batusangkar, 2021)
This study discusses the implementation of the political rights of disability voters in the 2019 simultaneous elections in Tanah Datar District according to the Disability and Fiqh Law Siyasah Dusturiyah. This type of research is field research in which materials are collected through interviews and documentation. The method used is a sociological juridical research method. Theories used are general election theory, political rights theory, disability political rights theory and siyasah dusturiyah fiqh theory. From the results of the research that the author did, it can be concluded that the implementation of fulfilling the political rights of persons with disabilities in the 2019 Simultaneous Elections in Tanah Datar District has not been carried out optimally. The obstacle faced by KPU in implementing the political rights of persons with disabilities is the difficulty in providing socialization to persons with disabilities. A review of fiqh siyasah dusturiyah on the implementation of the political rights of persons with disabilities was carried out by the Ahlu Halli Wal Aqdi institution which is an institution to accommodate the aspirations of the people. The fulfillment of political rights of persons with disabilities in the election is not in accordance with the fiqh siyasah dusturiyah.